Cannabinoids in Glioblastoma Therapy: New Applications for Old Drugs - Dumitru, Claudia A.; Sandalcioglu, I. Erol; Karsak, Meliha (Frontiers in Molecular Neuroscience, 2018)
Glioblastoma (GBM) is the most malignant brain tumor and one of the deadliest types of solid cancer overall. Despite aggressive therapeutic approaches consisting of maximum safe surgical resection and radio-chemotherapy, more than 95% of GBM patients die within 5 years after diagnosis. Thus, there is still an urgent need to develop novel therapeutic strategies against this disease. Accumulating evidence indicates that cannabinoids have potent anti-tumor functions and might be used successfully in the treatment of GBM. This review summarizes the latest findings on the molecular effects of cannabinoids on GBM, both in vitro and in (pre-) clinical studies in animal models and patients. The therapeutic effect of cannabinoids is based on reduction of tumor growth via inhibition of tumor proliferation and angiogenesis but also via induction of tumor cell death. Additionally, cannabinoids were shown to inhibit the invasiveness and the stem cell-like properties of GBM tumors. Recent phase II clinical trials indicated positive results regarding the survival of GBM patients upon cannabinoid treatment. Taken together these findings underline the importance of elucidating the full pharmacological effectiveness and the molecular mechanisms of the cannabinoid system in GBM pathophysiology.